2020
DOI: 10.1093/ntr/ntaa066
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Smokers Receiving Opioid Agonist Therapy Have an Elevated Nicotine Metabolite Ratio: A Replication Study

Abstract: Introduction Pregnant women exposed chronically to opioids smoked more cigarettes per day (CPD) and had a higher nicotine metabolite ratio (NMR), 3-hydroxycotinine/cotinine, a biomarker of nicotine metabolism and clearance, than those not receiving opioids. We examined CPD and NMR in a group of pregnant smokers, a quarter of whom were receiving opioid agonist therapy (OAT). Aims and Methods Pregnant smokers recruited to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Based on the limited number of studies reported to date, it is clear further investigation is needed to examine the interactions among depression and/or anxiety [ 76 ] and tobacco consumption, opioid exposure, and NAS outcomes. Recent evidence showed that women who are pregnant and on opioid agonist therapy had a higher nicotine metabolite ratio compared to women who are pregnant but not with OUD [ 77 ]. Further research is necessary to examine a difference in the nicotine metabolite ratio between methadone and buprenorphine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the limited number of studies reported to date, it is clear further investigation is needed to examine the interactions among depression and/or anxiety [ 76 ] and tobacco consumption, opioid exposure, and NAS outcomes. Recent evidence showed that women who are pregnant and on opioid agonist therapy had a higher nicotine metabolite ratio compared to women who are pregnant but not with OUD [ 77 ]. Further research is necessary to examine a difference in the nicotine metabolite ratio between methadone and buprenorphine exposure.…”
Section: Discussionmentioning
confidence: 99%